Apple peel atresia: a case report - Balineni, Pradeep; Kamal, Shruthi; Manickam, Prasanna; Shivaji, Keerthana (International Surgery Journal, 2019)
A 3 days old child presented with chief complaints of bilious vomiting and abdominal distention since few hours duration. Prenatal history revealed mother to be polyhydraminos and pregnancy induced hypertensive was on treatment with labetolol. Baby was a term, emergency lscs delivery. On examination baby was active, alert and with fair hydration. On per abdominal examination abdomen was distended and dilated bowel loops were seen. On per rectal wash pale jelly stools were expelled. Baby was taken up for emergency laprotomy and found to be having illeal atresia for which resection and anastamosis is done. Post operatively baby was doing well with satisfactory weight gain. Intestinal atresias are the major cause of intestinal obstruction in cases of neonates. They may be illeal or duodenal atresia. It is hypothesized to be occurring due intrauterine vascular assault and failure of recanalization. Babies present with vomiting and abdominal distention with mother having a positive history of polyhydraminos. On examination there will be abdominal distention with dilated bowel loops. X-rays would show dilated bowel loops and ultrasound shows decreased peristalisis in the bowel loops. Emergency laprotomy and surgical resection is the treatment of choice.